A Study And Development Of Digital Control Technique For Power Factor Correction Using Pre-Calculated Algorithm With A Low Cost 8-Bit Microcontroller - Liau , Wei Chun (2013)

(untitled)
The quality of distributed electrical power has become an acute concern in recent years. In order to comply with the requirements of international standards of harmonics emission in most of the AC-DC switched mode power supply, power factor correction is essential. Power factor correction in switched mode power supply has been implemented with analog controller conventionally. The mature manufacturing technologies in digital devices has led to the proliferation of powerful yet low cost digital controllers and enable the possibility of digital power factor correction implementation in a more competitive way. A digital control technique for power factor correction using pre-calculated algorithm with a low cost 8-bit microcontroller is studied and presented in this paper. Based on this technique, the duty cycles for half a line period are computed offline and stored into the device memory. A nearly unity power factor can be achieved based on the AC voltage line synchronization with the look up table in the memory at specific operating point. The primary advantages of this strategy are neither current measurement nor powerful yet expensive digital device are required. A prototype of boost power factor correction controlled by an 8-bit microcontroller development board was set up to implement the proposed technique. Both simulation and experimental results are showing positive trend that the proposed strategy for power factor correction achieves near unity power factor.